Low-Cost LoRaWAN Solution for Groundwater Monitoring in Peatlands - Usman, Saifudin; Atimi, Rizqia Lestika; Anhar, Muh; Susanto, Anto (Universitas Bina Darma, 2024)
Some efforts made in restoring peatlands include moisture restoration, replanting, hydrological restoration, monitoring, and evaluation using technology to obtain periodic condition data. The implementation of the Water Level Logger (WLL) for monitoring groundwater levels in peatlands still faces issues because the sensor installation points are not served by cellular communication networks for data transmission. This research aims to implement a Low Power Wide Area Network (LPWAN) as a low-cost infrastructure used in applications for monitoring water levels in peatland. The method in this research is an approach to develop LoRaWAN gateway devices and servers using ChirpStack, equipped up to the application layer as supporting infrastructure for self-hosted groundwater level monitoring tools integrated with a time-series database and displaying measurement data on a dashboard periodically. Based on the tests, the average measurement of the Received Signal Strength Indicator (RSSI) obtained at the farthest distance of 3 km was -116 dBm, where the RSSI value also decreased with each additional distance, and the Line-of-Sight (LOS) condition significantly affected the RSSI value. This research shows that a real-time peat groundwater monitoring system has been successfully built at a low cost using self-hosted LoRaWAN gateways and servers, while maintaining reliability.